The Combination Impact of Various Rates Of (N, P, K) Fertilizers on The Critical Point Concentration and Nutrient Balance of the (NPKS) In the Local Red Onion Leaf - Saeed, Dilzar Faiz; Dizayee, Alwand Tahir (International Journal of Membrane Science and Technology, 2023)
The research was taken place in Grdarash field the experimental farm of the College of Agriculture Engineering Science, Salahaddin University Erbil . Spilt-spilt plot design was used in the field with different NPK-fertilizer applications [ Nitrogen ( 0 , 40 , 80, 160 ) , Phosphorus ( 0 , 80 , 160 ) and Potassium ( 0 , 50 , 100 ) Kg ha -1 ] .The amount of Macro and Micro nutrients are excessive which used in Onion crop production . Nutrient balance impacted the crop production and quality. This study aimed to know the influence of the different rates of Nitrogen, Phosphorus &Potassium on the onion-yield to establish Nutrient Indexes and critical points concentrations for the elements (N P K S) , by using foliar analysis , so we can obtain the conditions of the elements-concentration in the leaf of the crop ( balance , imbalance , deficiencies , excessive ). The results show that there was high Significant interaction between (N P K) elements and Onion bulb yield. The best combination between Potassium and Nitrogen elements was (K50 N40) between Potassium and Phosphorus was (K50 P80). The treatment K1 P2 N 1 (K 50 , P 160 & N 40 Kg ha-1 ) has the highest Significant Onion-yield and recorded the best interaction between the ( Nitrogen , Phosphorus , Potassium ) elements .The critical concentration points for the Nutrients ( N P K S ) were ( 2.65 , 0.10 , 2.14 , 1.36 ) % respectively . The N-indexes, P-indexes, K- indexes and S-indexes ranged from (- 20.18 to 21.38 ) , ( - 27.30 to 17.07 ) , ( - 20.61 to 14.55 ) , ( - 11..22 to 23.11 ) respectively .